PENGARUH PENGGUNAAN TELEPON SELULER TERHADAP MINAT BACA PESERTA DIDIK PADA MATERI TEKS HIKAYAT - Sakdullah, Sakdullah; Lamusiah, Siti; Nurwahidah, Nurwahidah (Universitas Islam Ahmad dahlan, 2023)
Interest in reading is very necessary to support the knowledge that students must master. Reading is certainly a habit that all students in Indonesia must have. Interest in reading grows in every student, so to increase interest in reading each individual needs awareness. This research aims to determine the effect of using cellular telephone communication tools on students' reading interest in class X saga text material at SMK Negeri 3 Bangkalan. This research uses qualitative research by conducting interviews with 2 teachers as informants. Cell phone communication tools influence students' reading interest in saga text material in class.